Multiple Intelligence Theory in the Perspective of Islamic Education: A Case Study at Salafiyah Wustho Islamic Centre Bin Baz Yogyakarta - Nashihin, Husna; Supratama, Riky; Prastowo, Andi; Mursyidah, Naila Nur Khoiriyah (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2024)
This study discusses the Theory of Multiple Intelligence in the Perspective of Islamic Education and its implementation at Salafiyah Wustho Islamic Centre Bin Baz Yogyakarta. Based on the concept of multiple intelligences developed by Howard Gardner, this research aims to explore the extent to which the theory of multiple intelligences aligns with the perspective of Islamic education. Through a qualitative method involving interviews, observations, and data analysis using the Miles and Huberman model, this study highlights the application of the theory of multiple intelligences in Islamic religious education at the institution. The findings of this research are expected to provide a deeper understanding of how the concept of multiple intelligences can enhance the effectiveness of Islamic religious education and comprehend the cognitive and emotional potentials of each individual in the context of Islamic education.